2010
DOI: 10.1111/j.1399-3046.2010.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of pediatric living donor liver transplantation at a single institution

Abstract: There have only been a few studies on the long-term outcomes and prognostic factors after pediatric LDLT. We conducted a retrospective, single-center assessment of the outcomes as well as the demographic and clinical factors that influenced the poor outcomes in 113 children aged <16 (median age 21 months; 6 months-15.5 yr) who underwent 115 LDLTs, predominantly for biliary atresia (60.9%) and FHF (14.8%), between 1994 and 2006 at Asan Medical Center. Left lateral segment or left lobe grafts were implanted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
(57 reference statements)
4
31
1
Order By: Relevance
“…Although no significant survival difference was observed, we analyzed the factors associated with survival outcome according to the age group. The overall survival outcomes of our study including both age groups were acceptable compared to other previously reported papers (4-6); the 1, 5, and 10 yr graft survival rates were 92%, 88%, and 86%, and the patient survival rates were 93%, 90%, and 87%, respectively.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although no significant survival difference was observed, we analyzed the factors associated with survival outcome according to the age group. The overall survival outcomes of our study including both age groups were acceptable compared to other previously reported papers (4-6); the 1, 5, and 10 yr graft survival rates were 92%, 88%, and 86%, and the patient survival rates were 93%, 90%, and 87%, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…Several large scale studies for the outcome of pediatric LT have been published in other countries (2-6). For these studies, the disease categories and outcome of LT as well as the physiologic changes of the children significantly differed according to the age at the time of the transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Despite measures that included the Kasai operation and endoscopic interventions, many of these children died or underwent liver transplantation. Liver transplantation is the best treatment for children with end-stage liver disease [21], with surgical intervention, such as the Rex shunt, a further possibility for children with EHPVO [5]. Second, there is no evidence that endoscopic intervention can prevent hepatopulmonary syndrome or portopulmonary hypertension [22].…”
Section: Discussionmentioning
confidence: 99%
“…Given the presence of aggravated hepatic encephalopathy, azotemia, and that the patient was refractory to medical treatments, she received a living-donor liver transplantation from her aunt on hospital day 9. The detailed care of preliver and postliver transplantation and care of acute liver failure in our program was described elsewhere4,5).…”
Section: Case Reportmentioning
confidence: 99%